Contribution on the Life and Work of Composer Jan Urban - MARIĆ, Domagoj; GRUBER, Gerold (Anafora, 2023)
Jan Urban (1875 – 1952) was a Czech composer who spent most of his life in the South Slav area. In 1899, he arrived in the Kingdom of Serbia, where he was employed as a military band conductor until 1918, and subsequently continued the same service in the Kingdom of Serbs, Croats, and Slovenes and the Kingdom of Yugoslavia. As a military musician, from his original arrival in Serbia until his retirement in 1941, he participated in the two Balkan Wars as well as the First World War. His service during this period made it possible for Urban to work in a variety of different cities. Osijek would be the one city among all others that stood out with its own rich musical traditions, similar to his native Prague, and its unique position within the Habsburg Monarchy until 1918. Among Urban’s most significant works are two operas (Mother and Djul Beaza), two operettas (Iguman’s Sin and Terpsichore), various orchestral compositions (nine “Serbian Dances,” thirteen “Saltarelli,” and twenty overtures and suites), more than fifty piano pieces published before the First World War, and many others.